2019
DOI: 10.1016/j.neuroimage.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory dopaminergic-cholinergic interactions in conflict processing: Evidence from patients with Parkinson's disease

Abstract: Executive functions are complex both in the cognitive operations involved and in the neural structures and functions that support those operations. This complexity makes executive function highly vulnerable to the detrimental effects of aging, brain injury, and disease, but may also open paths to compensation. Neural compensation is often used to explain findings of additional or altered patterns of brain activations by older adults or patient populations compared to young adults or healthy controls, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“… 36 , 37 Bohnen et al and Kim et al expanded on these findings by showing both independent and interactive roles of the cholinergic and dopaminergic systems in cognitive functioning in PD. 17 , 38 In the context of dopaminergic losses, preservation or even upregulation of cholinergic innervation may help preserve cognitive functioning. 39 In addition, Liu et al reported increased cortical acetylcholinesterase activity related to LRRK2 gene mutation in (premanifest) PD.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Bohnen et al and Kim et al expanded on these findings by showing both independent and interactive roles of the cholinergic and dopaminergic systems in cognitive functioning in PD. 17 , 38 In the context of dopaminergic losses, preservation or even upregulation of cholinergic innervation may help preserve cognitive functioning. 39 In addition, Liu et al reported increased cortical acetylcholinesterase activity related to LRRK2 gene mutation in (premanifest) PD.…”
Section: Discussionmentioning
confidence: 99%
“…34 For example, Kim and colleagues showed that cortical cholinergic integrity was a stronger predictor of conflict processing in PD patients with relatively low caudate dopaminergic function. 35 These findings imply also a more-nuanced perspective that diverges from the dual-syndrome hypothesis given that the cholinergic system may make an important contribution to executive dysfunction in PD.…”
Section: Cholinergic Dysfunctionmentioning
confidence: 96%
“…Conversely, combined dopaminergic and cholinergic neurotransmitter system losses may aggravate cognitive, especially executive, function deficits and jointly increase the risk of conversion to PDD . For example, Kim and colleagues showed that cortical cholinergic integrity was a stronger predictor of conflict processing in PD patients with relatively low caudate dopaminergic function . These findings imply also a more‐nuanced perspective that diverges from the dual‐syndrome hypothesis given that the cholinergic system may make an important contribution to executive dysfunction in PD.…”
Section: Molecular Imaging Of Pdmentioning
confidence: 99%
“…Recently, we reported on the so-called ‘compensatory’ hypothesis to better understand dynamic changes in both dopaminergic and cholinergic systems in PD (N. I. Bohnen et al, 2015; Kim, Bohnen, Muller, & Lustig, 2018). The ‘compensatory’ hypothesis posits that frontostriatal dopaminergic losses may lead to compensatory reliance in cortical cholinergic circuits.…”
Section: Cholinergic System Changes In Pd and Parkinsonian Dementiamentioning
confidence: 99%